Molecular mechanisms, current management and next generation therapy in myeloma bone disease. Issue 1 (2nd January 2018) - Heusschen, Roy; Muller, Joséphine; Duray, Elodie; Withofs, Nadia; Bolomsky, Arnold; Baron, Frédéric; Beguin, Yves; Menu, Eline; Ludwig, Heinz; Caers, Jo
Abstract: Multiple myeloma (MM) bone disease is a major cause of morbidity and mortality in MM patients and persists even in patients in remission. This bone disease is caused by an uncoupling of bone remodeling, with increased osteoclast and decreased osteoblast activity and formation, culminating in lytic bone destruction. Bisphosphonates are the current standard of care but new therapies are needed. As the molecular mechanisms controlling MM bone disease are increasingly well understood, new therapeutic targets are extensively explored in the preclinical setting and initial clinical trials with novel compounds now show promising results. In this review, we will provide a comprehensive overview of the biology of MM bone disease, summarize its current clinical management and discuss preclinical and clinical data on next generation therapies.